Mathematical modelling and experimental investigation on sun and solar drying of white mulberry - Akpinar, E. Kavak (Korean Soc Mechanical Engineers, 2008)
The drying kinetics of white mulberry was investigated in a solar dryer with forced convection and under open Sun with natural convection. The constant rate period is absent from the drying curve. The drying process took place in the falling rate period. The drying data were fitted to the different mathematical models. The performance of these models was investigated by comparing the determination of coefficient (R), reduced chi-square (chi(2)) and root mean square error (RMSE) between the observed and predicted moisture ratios. Among these models, the drying model developed by Logarithmic model showed good agreement with the data obtained from the experiments in the solar dryer with forced convection drying mode. The Verma et al. model has shown a better fit to the experimental mulberries data for open sun drying with natural convection mode than the other models. The effective moisture diffusivity values were estimated from Fick's diffusional model. These values were 3.56x10(-9) m(2)/s for solar drying and 2.40 x 10(-9) m(2)/s for open sun drying.
Keywords: solar drying; natural sun drying; forced drying; thin layer drying models; white mulberry